Evaluation of the quality of nursing care - Lemonidou, Chryssoula; Merkouris, Anastasios (My University, 1999)
Today, despite the a great interest for the evaluation and the improvement of the health care services the concept of quality remains undefined. All the researchers agree that the concept of quality is dimensional and complex and the identification of the features which compound the concept of quality is very difficult. This article discuss the most important obstacles in the evaluation process and represents a theoretical framework for the measurement of the quality of nursing care , proposing specific areas of great interest.